Determination of E-Commerce Shopping Intentions among Students in Manado City: A Theory of Planned Behavior Approach: JEL Classification: D12, D91, M31, O33, L81 - Modaso, Paske Victory; Setlight, Durand Fernandito Freddy; Barek , Titya Advianti P. (Pusat Studi Pembangunan dan Pemberdayaan, 2026)
This study aims to analyze the determinants of e-commerce shopping intentions among students in Manado City using the Theory of Planned Behavior (TPB) framework. A quantitative explanatory approach was employed, with data collected through structured questionnaires distributed to 90 school and university students who had prior experience using e-commerce platforms. The data were analyzed using multiple linear regression with SPSS. The results indicate that attitude, subjective norm, and perceived behavioral control all have a positive and significant effect on students’ e-commerce shopping intentions. Attitude was found to be the strongest predictor, followed by perceived behavioral control and subjective norm. The regression model demonstrates strong explanatory power, with the TPB variables explaining 71.7% of the variance in shopping intention. These findings confirm the relevance of the Theory of Planned Behavior in explaining e-commerce shopping intentions among students in a regional urban context. The study contributes to the literature on digital consumer behavior by providing empirical evidence from Manado City and offers practical insights for e-commerce platforms and educational stakeholders in designing strategies that align with students’ psychological and social characteristics.